Role of proximal gut exclusion from food on glucose homeostasis in patients with Type 2 diabetes. Issue 12 (19th July 2013) - Cohen, R.; le, C. W.; Papamargaritis, D.; Salles, J. E.; Petry, T.; Correa, J. L.; Pournaras, D. J.; Galvao Neto, M.; Martins, B.; Sakai, P.; Schiavon, C. A.; Sorli, C.
Abstract Aims To report Type 2 diabetes‐related outcomes after the implantation of a duodenal‐jejunal bypass liner device and to investigate the role of proximal gut exclusion from food in glucose homeostasis using the model of this device. Methods Sixteen patients with Type 2 diabetes and BMI <36 kg/m2 were evaluated before and 1, 12 and 52 weeks after duodenal‐jejunal bypass liner implantation and 26 weeks after explantation. Mixed‐meal tolerance tests were conducted over a period of 120 min and glucose, insulin and C‐peptide levels were measured. The Matsuda index and the homeostatic model of assessment of insulin resistance were used for the estimation of insulin sensitivity and insulin resistance. The insulin secretion rate was calculated using deconvolution of C‐peptide levels. Results Body weight decreased by 1.3 kg after 1 week and by 2.4 kg after 52 weeks (P < 0.001). One year after duodenal‐jejunal bypass liner implantation, the mean (sem) HbA1c level decreased from 71.3 (2.4) mmol/mol (8.6[0.2]%) to 58.1 (4.4) mmol/mol (7.5 [0.4]%) and mean (sem) fasting glucose levels decreased from 203.3 (13.5) mg/dl to 155.1 (13.1) mg/dl (both P < 0.001). Insulin sensitivity improved by >50% as early as 1 week after implantation as measured by the Matsuda index and the homeostatic model of assessment of insulin resistance (P < 0.001), but there was a trend towards deterioration in all the above‐mentioned variables 26 weeks after explantation. Fasting insulin levels, insulin area under the curve, fasting C‐peptide, C‐peptide area under the curve, fasting insulin and total insulin secretion rates did not change during the duodenal‐jejunal bypass liner implantation period or after explantation. Conclusions The duodenal‐jejunal bypass liner improves glycaemia in overweight and obese patients with Type 2 diabetes by rapidly improving insulin sensitivity. A reduction in hepatic glucose output is the most likely explanation for this improvement.